2022
DOI: 10.1177/10870547221131979
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of ADHD Among Children in the United States: Validity and Reliability of Parent Report of Provider Diagnosis

Abstract: Objective: To evaluate the appropriateness of parent-reported diagnosis of ADHD as a surveillance tool. Method: We assessed agreement over time and concordance of parent-reported diagnosis against Diagnostic and Statistical Manual (DSM)-based criteria. We compared concordance of diagnosis and DSM-based criteria by child characteristics, including treatment. Results: Among parents who reported their child had ADHD, 95.7% reported it again 2 years later. Comparing diagnosis with DSM-based criteria, specificity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, a previous study showed that parent reported ADHD diagnosis resulted in similar prevalence estimates compared to administrative claims data suggesting convergent validity of ADHD prevalence from both these sources (Visser et al, 2014). Parent-reported ADHD diagnosis can be reliable over time and often discrepancies between parent-reported diagnosis and DSM-based criteria is a reflection of milder symptoms or treated ADHD (Cree et al, 2022). Parent-reported ADHD and severity from the NSCH is used for national ADHD prevalence estimates for the Centers for Disease Control and Prevention (Danielson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study showed that parent reported ADHD diagnosis resulted in similar prevalence estimates compared to administrative claims data suggesting convergent validity of ADHD prevalence from both these sources (Visser et al, 2014). Parent-reported ADHD diagnosis can be reliable over time and often discrepancies between parent-reported diagnosis and DSM-based criteria is a reflection of milder symptoms or treated ADHD (Cree et al, 2022). Parent-reported ADHD and severity from the NSCH is used for national ADHD prevalence estimates for the Centers for Disease Control and Prevention (Danielson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have consistently reported high internal consistency and reliability of total ADHD‐RS scores in both parent and teacher rating scales (So et al, 2002; Tahıllıoğlu et al, 2021). Recent studies across diverse cultural contexts and age groups have demonstrated the reliability of ADHD‐RS scores, as evidenced by high reliability and construct validity in Sudan (Alhossein, 2022), notable efficacy and sensitivity in diagnosis in Korea (Won, 2020), and consistent high reliability in the United States (Cree, 2023). Additionally, recent evidence supports the reliability of the ADHD‐RS as self‐reports in adolescence (Green et al, 2019) and adults (Brevik et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) is one of the most common neurodevelopmental disorders in childhood and adolescence, affecting ~5.9% of children worldwide, ~8.4% in USA, ~2.9% in Europe and ~6.3% in China. [1][2][3][4][5] The main characteristics of children with ADHD are age-inappropriate attention distraction, reduced attention span, and excessive activity and emotional impulses regardless of the occasion. 6 Three presentations of ADHD were listed in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V), including predominantly inattentive (ADHD-I), predominantly hyperactive/impulsive (ADHD-H), and combined presentation (ADHD-C).…”
Section: Introductionmentioning
confidence: 99%